Effects of a polyphenol-rich extract blend, probiotics, and hydrolyzed fiber on quality of life and gut health markers in patients with irritable bowel syndrome—A randomized, double-blind, placebo-controlled trial - Adrianna Wierzbicka; Adrianna Wierzbicka; Barbara Khaidakov; Oliwia Zakerska-Banaszak; Paulina Andrzejewska; Alina Baturo; Paulina Kowalczyk; Krzysztof Lemke; Agnieszka Dobrowolska; Marzena Skrzypczak-Zielinska; Dorota Mankowska-Wierzbicka (Frontiers in Nutrition)
IntroductionIrritable bowel syndrome (IBS) is the most prevalent functional bowel disorder impacting around 5%−10% of the general population worldwide. The pathogenesis remains unclear, however alterations in gut-brain axis play a critical role. We aimed to investigate the therapeutic potential of a novel synbiotic formulation comprising of partially hydrolyzed guar gum (PHGG), specific probiotic strains (Bifidobacterium and Saccharomyces boulardii), and double-standardized, polyphenol-rich blend of extracts from Aronia melanocarpa and Sambucus nigra in patients with IBS.MethodsA total of 47 patients with IBS were randomly assigned to three groups and followed over a 2-month study period. Group I (n = 14) received placebo capsules, Group II (n = 14) took one placebo capsule along with a probiotic formulation and PHGG, Group III (n = 19) received probiotic formulation, PHGG and polyphenol-rich fruit extracts blend. The IBS-quality of life (QoL) questionnaire was completed by all participants at baseline and after 2 months. Serum levels of IL-6, IL-8, TNF-α, I-FABP-2, GM-CSF and stool concentrations of short-chain fatty acids (SCFAs) and zonulin were evaluated before and after intervention.Results and conclusionsThis study demonstrated a significant improvement in QoL in individuals receiving the complete formulation combination (Group III). The largest decrease in score was observed in dysphoria, with median differences of −5 in Group III (p = 0.0021), −3 in Group II (p = 0.0155), and −1 in the control Group I (p = 0.0338). Significant correlations were found in Groups II and III between supplementation and serum concentrations of IL-8, TNF, and GM-CSF (p < 0.05). A significantly higher concentration of all SCFAs was seen after intervention in Group III compared to control Group I.